University-Industry Collaboration (UIC) and the Resources-Based View (RBV) - Imaduddin, Abidin; Mohd Rashid, Ab Hamid; Yap, Chui Yan; Ida Rizyani, Tahir; Norlida, Ramli (ICARB, 2015)
Small and medium enterprises (SMEs) is known as the entity that always in need for support due to disadvantages of business from entity. Indeed, knowledge transfer is seen as a major resources of long-term growth of SMEs. Besides, technology transfer to the firm is critical and significant for SMEs performance. The purpose of this paper is to improve understanding of University Industry Collaboration (UIC) concept and how its function can uplift the performance of SMEs. The UIC will consider knowledge transfer and technology transfer activities from university to SMEs. This paper also will discuss on the Resources-based View (RBV) Theory and its links between UIC and SMEs performance. This paper presents literature analysis concerning this research topic and explores the meaning of UIC, knowledge transfer and technology transfer, and RBV.